2021
DOI: 10.1002/cam4.3797
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of venous thromboembolism after standard treatment in patients with epithelial ovarian cancer in Korea

Abstract: Background Venous thromboembolism (VTE) is a hospital‐associated severe complication that may adversely affect patient prognosis. In this study, we evaluated the incidence of VTE and its risk factors in patients with epithelial ovarian cancer (EOC). Methods We retrospectively analyzed the electronic health record data of 1268 patients with EOC who received primary treatment at the National Cancer Center, Korea between January 2007 and December 2017 to identify patients who developed VTE. Demographic, clinical,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…However, Ohashi et al, (2020) reported an incidence of VTE in Japanese patients with gynecologic malignancy at 5.5 (50/906) percent. The finding from the current study was in lieu with Ohashi's (5.5 %), Shin's (9.6%) and Kahr's (11%) literature, the incidence from their work might be from the inclusion of both operative and non-operative case (Ohashi et al, 2020;Shin et al, 2021, Kahr et al, 2021. In contrast, Barber et al reported from the USA in 2016 that the incidence of VTE among gynecologic malignancy operations was 1.8 percent.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…However, Ohashi et al, (2020) reported an incidence of VTE in Japanese patients with gynecologic malignancy at 5.5 (50/906) percent. The finding from the current study was in lieu with Ohashi's (5.5 %), Shin's (9.6%) and Kahr's (11%) literature, the incidence from their work might be from the inclusion of both operative and non-operative case (Ohashi et al, 2020;Shin et al, 2021, Kahr et al, 2021. In contrast, Barber et al reported from the USA in 2016 that the incidence of VTE among gynecologic malignancy operations was 1.8 percent.…”
Section: Discussionsupporting
confidence: 62%
“…Compared to the study from Japan, Korea and Denmark, the prevalence of VTE in gynecologic cancer patients varied from 5.5 to 11 percent (Ohashi et al, 2020;Shin et al, 2021, Kahr et al, 2021. In year 2021, Shin's and Kahr's groups had reported the prevalence of VTE in ovarian cancer patients among Koreans and Danes as 9.6 (122/1268) and 11(551/4991) percent (Shin et al, 2021;Kahr et al, 2021). However, Ohashi et al, (2020) reported an incidence of VTE in Japanese patients with gynecologic malignancy at 5.5 (50/906) percent.…”
Section: Discussionmentioning
confidence: 88%
“…45 Among patients with EOC, VTE is the most prevalent cardiovascular event during the initial treatment, with 85% occurring within 1 year after EOC diagnosis. 46 Other studies showed that the development of VTE within 2 years of cancer diagnosis is a significant risk factor of reduced survival, 2 and the 1-year survival rate of patients with cancer with VTE was 12%, significantly lower than 36% in the control group. 47 Our study, rooted in DL algorithms, excels in providing personalized VTE risk predictions at specific time points during the follow-up period.…”
Section: Discussionmentioning
confidence: 95%